2008
DOI: 10.1117/12.765711
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of multispectral imaging for the mapping of pigments in paintings

Abstract: Compared with colorimetric imaging, multispectral imaging has the advantage of retrieving spectral reflectance factor of each pixel of a painting. Using this spectral information, pigment mapping is concerned with decomposing the spectrum into its constituent pigments and their relative contributions. The output of pigment mapping is a series of spatial concentration maps of the pigments comprising the painting. This approach was used to study Vincent van Gogh's The Starry Night. The artist's palette was appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…In such a study a pixel may be several metres across and cover both a patch of grass and some tarmac, whereas for paint materials this is not the case, as pigments are uniformly dispersed in the binding media and the spectral response is not a simple linear mixture of the reflectance. The Kubelka-Munk (KM) theory is more appropriate [1,9] and is used in the paint industry to calculate the ratios of paints to match a given colour [1]. The effect of binding medium, particle size, and concentration have been systematically studied and dirt and varnish can also have an effect [1].…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
See 3 more Smart Citations
“…In such a study a pixel may be several metres across and cover both a patch of grass and some tarmac, whereas for paint materials this is not the case, as pigments are uniformly dispersed in the binding media and the spectral response is not a simple linear mixture of the reflectance. The Kubelka-Munk (KM) theory is more appropriate [1,9] and is used in the paint industry to calculate the ratios of paints to match a given colour [1]. The effect of binding medium, particle size, and concentration have been systematically studied and dirt and varnish can also have an effect [1].…”
Section: Hyperspectral Imagingmentioning
confidence: 99%
“…d13. For the purpose taking this photo of the equipment the room lights have been left on, during a scan the room lights are always off 9 …”
Section: Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…This is sometimes referred to as the single constant KM theory. Since the aim here is to identify the pigments in a mixture, the concentrations of the single pigments were set as free parameters to find the best non-negative least squared fit of the predicted spectrum to the actual measured spectrum of the mixture for each combination of reference pigments [67] [79]. Liang et al [67] showed that the method worked even for pigment mixtures without the addition of white pigments, except in cases where pigments with high absorption or very low scattering are involved.…”
Section: Pigment Identificationmentioning
confidence: 99%